Low-Frequency Raman Spectroscopic Monitoring of Supramolecular Structure in H-Bonded Liquids. (4th March 2014) - Kuzkova, Nataliia; Yakunov, Andrey; Bilyi, Mykola
Abstract : Effective density of vibrational states in H-bonded liquids was measured by Raman scattering method. Actuality of a low-frequency part of the spectrum of the intermediate (fracton) region, which obeys a power law, indicates the correct application of the percolation model. The dependence of exponent on binary solutions concentration has been studied. Existence of correlation of the fractal structure parameter and dynamic viscosity has been noted.